Determination of Factors Affecting Taxpayer Compliance with Vehicle Tax at the Samsat Pedurungan, Semarang City - Ericke Fridatien; Ahmad Sahri Romadon (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2026)
This study aims to determine whether Taxpayer Awareness, Tax Knowledge, and Tax Sanctions influence the Compliance of Motor Vehicle Taxpayers at the Pedurungan Samsat Office in Semarang for the 2022–2024 period. Taxes are a mandatory contribution used by the government for national development, yet taxpayer compliance remains a challenge affecting regional revenue optimization. This research employs a quantitative research method. The data used are primary data obtained from questionnaires distributed to respondents. The population in this study consists of Motor Vehicle Taxpayers registered at the Pedurungan Samsat Office in Semarang. A total of 97 respondents were selected as samples using the accidental sampling method. The analytical method used is multiple linear regression analysis to test the hypotheses.The findings indicate the existence of significant factors influencing compliance. Specifically, the results of this study indicate that Taxpayer Awareness has a positive and significant effect on Taxpayer Compliance, and Tax Knowledge has a positive and significant effect on Taxpayer Compliance. However, Tax Sanctions have no effect and are not significant on Taxpayer Compliance. The study concludes that increasing taxpayer awareness and knowledge is crucial for improving compliance rates. It is suggested that the relevant authorities focus on socialization and education programs rather than solely relying on sanctions, which were found to be ineffective in this context.Keywords: Tax Agressiveness, Profitability, CSR, Company Size